The Influence of Competence, Compensation and Motivation on the Performance of Non-Permanent Employees - Syaifullah Syaifullah; Saifhul Anuar Syahdan; Riswan Yudhi Fahrianta; Rahmi Yatun; Christian Mukti Tama. S. (AIBPM Publisher, 2022)
The purpose of this study was to determine the effect of competence, compensation, and motivation on the performance of non-permanent employees. The research method used is explanatory which aims to test hypotheses about a causal relationship between the variables studied from 91 non-permanent employees at the Regional Secretariat of Tanah Laut Regency, South Kalimantan. The results show that competence does not affect the performance of temporary employees, compensation affects the performance of temporary employees, work motivation affects the performance of temporary employees, competence, compensation and work motivation simultaneously affect the performance of temporary employees.Â Â Keywords: competence, compensation, motivation, non-permanent employee performance